Immersive capability and spatial presence in virtual reality photo-based tours: implications for distance education - Roberto Bacani Figueroa Jr (AAOU Journal)
Purpose – The purpose of this study is to describe an educational virtual reality (VR) photo-based tour used in an online course and investigate the influence of immersive capability on the dimensions of spatial presence and their relationship with learning-related variables. Design/methodology/approach – The study employs a descriptive and an experimental methodological approach. The research objectives were achieved using a two-group (n1 = 29 and n2 = 30) experiment, employing descriptive statistics, t-test and correlation analysis. Findings – The t-test revealed that the immersive capability had a significant effect on the sense of physical space (SP) , Engagement (EN) and negative effects (NE) dimensions. Correlations between the dimensions of spatial presence were found to confirm reports from the literature. Furthermore, some of the dimensions were found to be correlated with motivational and learning variables. Research limitations/implications – The study reported the results of a one-off experiment among 59 participants. While the results were promising, a longitudinal qualitative study could confirm the results in an actual distance learning context. Practical implications – The study confirmed that adding VR photo-based tours as learning activities may enhance the learning experience of distance learners. Social implications – The study shared a case of a learning activity that can be employed for flexible education. Virtual tours can support the need for context-based learning that the geographical or political constraints may limit. Originality/value – While the paper confirms previous reports on the benefits of using VR photo-based tours as learning activities, this paper has empirically shown the relationship between the dimensions of spatial presence and immersive capability in this specialized context.